China, the Rule of Law, and the Question of Obedience: A Comment on Professor Peerenboom - Pils, Eva (Hague Journal on the Rule of Law, 2015)
Commenting on Randall Peerenboom’s analysis of an October 2014 decision by China’s ruling Communist Party on legal reform, I make two points here. First, I argue that Peerenboom’s in my view inaccurate account of (positivistic and naturalist) liberal conceptions of law prevents him from understanding the implications of this decision’s deeply illiberal commitment to power concentration and Party supremacy over law. This account fails to appreciate the resources which liberalism offers to engage critically with the operation of a legal system such as that of China, where – as I point out drawing on my work on human rights lawyers – repression of legal and political rights advocacy have been worsening. Second, I suggest that both the Decision and Peerenboom’s analysis do not fully take into account the nature and scope of the challenges the Party-State is facing, especially the challenge arising from an increasing momentum for civic activism and civil disobedience.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Authoritarianism; China; Human rights; Liberalism; Repression; Rule of law